1997
DOI: 10.1002/jor.1100150310
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuous distraction on cartilage in a moving joint: An investigation on adult rabbits

Abstract: An animal model, using distraction force on adult rabbits, was developed to study the effects of nonweight-bearing on articular cartilage in a moving joint. Histologic evaluation was used to compare the morphology of chondrocytes, safranin O intensity, cartilage thickness, and structural changes between the test and contralateral joints. At 3 and 6 weeks, the chondrocytes in superficial and intermediate zones were round, with an increase in cellular volume density and mean cell volume and with less metachromas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 34 publications
0
19
1
Order By: Relevance
“…Application of an external fixator itself has been suspected to cause changes similar to OA (Hung et al 1997). Our results reveal that there is no significant effect of simple external fixation of the joints, and it can be used safely for fractures around osteoarthrotic joints.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Application of an external fixator itself has been suspected to cause changes similar to OA (Hung et al 1997). Our results reveal that there is no significant effect of simple external fixation of the joints, and it can be used safely for fractures around osteoarthrotic joints.…”
Section: Discussionmentioning
confidence: 53%
“…Nonarticulated distraction worsened the results very significantly, while simple external fixation or articulated distraction had no statistically significant effect on the osteoarthrotic cartilage (Table). Theoretically, these results are not surprising, as the continuous distraction in a moving joint causes morphological changes in chondrocytes prior to degeneration and the forces exerted on cells distort their shape and stimulate alteration in cellular biochemistry and matrix metabolism (Hung et al 1997). Contrary to our results, van Valburg et al (2000) found no difference between the histology of the cartilage of distracted and non-distracted knees.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, joint immobilization has harmful effects on both periarticular tissue and cartilage (Hung et al 1997). …”
Section: Discussionmentioning
confidence: 99%
“…With degeneration, the tribiology of the joint is affected, with areas of cartilage underloading 114 and bony overloading. 115,116 Metabolic, weight-bearing stresses and cartilage injury aggravate the changes caused by use and degeneration.…”
Section: Bone-related Candidatesmentioning
confidence: 99%